Reliability and short-term intra-individual variability of telomere length measurement using monochrome multiplexing quantitative PCR. - Sangmi Kim; Dale P Sandler; Gleta Carswell; Clarice R Weinberg; Jack A Taylor (PLoS ONE)
Background Studies examining the association between telomere length and cancer risk have often relied on measurement of telomere length from a single blood draw using a real-time PCR technique. We examined the reliability of telomere length measurement using sequential samples collected over a 9-month period. Methods and findings Relative telomere length in peripheral blood was estimated using a single tube monochrome multiplex quantitative PCR assay in blood DNA samples from 27 non-pregnant adult women (aged 35 to 74 years) collected in 7 visits over a 9-month period. A linear mixed model was used to estimate the components of variance for telomere length measurements attributed to variation among women and variation between time points within women. Mean telomere length measurement at any single visit was not significantly different from the average of 7 visits. Plates had a significant systematic influence on telomere length measurements, although measurements between different plates were highly correlated. After controlling for plate effects, 64% of the remaining variance was estimated to be accounted for by variance due to subject. Variance explained by time of visit within a subject was minor, contributing 5% of the remaining variance. Conclusion Our data demonstrate good short-term reliability of telomere length measurement using blood from a single draw. However, the existence of technical variability, particularly plate effects, reinforces the need for technical replicates and balancing of case and control samples across plates.